Clinical management of ectopic Cushing Syndrome in neuroendocrine neoplasms: a national survey - Laffi, Alice; Prinzi, Antonio; Di Dato, Carla; Feola, Tiziana; Medici, Margherita; Colao, Annamaria; Faggiano, Antongiulio; Lania, Andrea Gerardo Antonio (Frontiers in Endocrinology, 2025)
BackgroundEctopic Adrenocorticotropic Hormone (ACTH) Syndrome (EAS) is a complex disorder caused by ACTH-producing tumors located outside the pituitary gland. EAS is most commonly associated with neuroendocrine neoplasms (NENs), rare malignancies category. Due to the nonspecific symptoms, EAS is often misdiagnosed, contributing to increased morbidity and complicating clinical management. In Italy, access to diagnostic and therapeutic resources for EAS and NENs varies significantly by region. As part of the 2024–2025 NIKE (Neuroendocrine Tumors, Innovation in Knowledge and Education) initiative, a multidisciplinary group, including endocrinologists, oncologists, pathologists, and nuclear medicine experts, designed a national survey to assess awareness, diagnostic approaches, and management of EAS in Italian centers.MethodsA 50-items structured questionnaire was developed, covering 3 sections: respondents’ profile, diagnostic approaches, and treatment strategies. The survey was distributed as an anonymized form via email, with data collected from April to June 2025.ResultsSixteen Italian centers with NEN and EAS expertise participated. Most experts worked in European referral centers for rare tumors where the majority have an in-house, NEN-dedicated multidisciplinary team. Initial points of contact occurred most frequently in oncology (37.5%) and endocrinology (31.5%) clinics. A diagnostic delay was reported by 56% of respondent centers; hypokalemia was the most common presenting sign (93.8%). In 56.3% of centers, respondents reported that EAS was more commonly diagnosed before the detection of the underlying NEN, most frequently lung carcinoids or small/large cell cancers (87.5%). Regarding diagnostic practices, 56.3% of centers indicated the use of the 1 mg dexamethasone suppression test (DST), followed by the high-dose DST. The desmopressin test was considered outdated or replaceable by 43.8% of respondents. Regarding therapeutic approaches, respondents reported that upfront surgery was performed in up to 50% of centers, with preoperative bridging pharmacological therapy used to achieve eucortisolism. Osilodrostat was the most frequently preferred first-line treatment.ConclusionThis survey provides a valuable snapshot of EAS care in Italy, highlighting both strengths and areas for improvement. The findings underscore the need for a national, more structured referral network to ensure timely diagnosis and access to specialized care. These insights may guide national protocol harmonization in EAS management and better alignment with international standards.